Effective chair training methods for neuroscience research involving rhesus macaques (Macaca mulatta) - Mason, Stuart (J Neurosci Methods, 2019)
BACKGROUND: Neuroscience research using macaques remains fundamental in our endeavours to understand how the human brain functions. Applying the refinement principle of the 3Rs is essential to optimise the monkeys’ welfare and still produces high quality science. NEW METHOD: Here we document refinements in our training methods for acclimation to transport devices (i.e. primate chair or transport box) while working with 46 male rhesus macaques. Our training methods always used positive reinforcement training (PRT). However, PRT was sometimes combined with negative reinforcement training (NRT), but not pole and collar techniques, to successfully transfer each monkey from its home enclosure to its transport device. RESULTS AND COMPARISON WITH EXISTING METHODS: Training monkeys in pairs or groups, and starting their PRT training upon arrival within the unit reduced the days required to acclimate them. While the use of PRT is essential to establish a positive relationship with monkeys, NRT techniques are sometimes necessary, and are most effective when withdrawn immediately once the monkey makes the desired response, to reduce the days of acclimation. Once acclimatised to their chair, monkeys succeeded within 10 days to present their head voluntarily for neck-plating using PRT. Space reducers inside the chairs also facilitated head presentations for some monkeys. CONCLUSIONS: Acclimating (shaping) the monkeys to transport devices can be a stressful experience for monkeys and trainers. The adaptations to our training substantially reduced the days spent on this stage. We view this reduction in days as an effective implementation of the 3Rs (refinement) in monkey neuroscience research.